LANGUAGE VARIATION: AN ANALYSIS OF LANGUAGE VARIETIES USED BY EFL STUDENTS ON SOCIAL MEDIA CONTEXT - Emira Putri, Ambarwati; Jaya Putra, Nyoman Adi (Getsempena English Education Journal, 2024)
Language variation defined as a language use according the users, which differs based on the topic being discussed, the relationship between the speaker, the interlocutor, as well as the media of communication. This research focus on language variation used by the EFL students on social media. This research aimed to investigate the variation of language on social media specifically on Instagram and Facebook used by the EFL students. The design of this research was a descriptive qualitative method. The data collection was gained from observation, and documentation. The validity of the data used in this study was triangulation of sources, methods, and theory. The data analysis was gained by using Miles and Huberman theories. The result showed that there are some language variation used by the students on social media in term of dialect, colloquial language, gender, code, slang, code switching, and code mixing. The students are commonly applying a variety of unexpected language variations in the forms of acronyms, familiar phrases, and the use of local languages (sumbawanese) combined with the national language, English, even Arabic. Some might use English creatively, while others may struggle with grammar or vocabulary, leading to unique forms of expression that blend their English skills with local linguistic patterns. In addition, the EFL students use a wide range of languages on social media platforms especially Facebook and Instagram. Thus, the occurrence of language diversity is not only caused by non homogeneous speakers but also caused by the wide range of social interactions the speaker engage in.